Short fatigue cracks in austempered ductile cast iron (ADI) - Marrow, T; Cetinel, H (2000)
The growth of short fatigue cracks was investigated in an austempered ductile cast iron (wt% 3.6C, 2.5Si, 0.6Mn, 0.15Mo, 0.3Cu), austenitized at 870 °C and then austempered at 375 °C for 2 h. At stress amplitudes close to the fatigue limit endurance limit of 107 cycles, subcritical crack nuclei initiated at graphite nodules. The crack nucleus decelerated and arrested after propagating a short distance. The position of an arrested crack tip was characterized using an electron backscatter diffraction technique, demonstrating that short fatigue cracks in austempered ductile cast iron (ADI) can be arrested by boundaries such as those between ausferrite sheaves or packets and prior austenite grains. Refinement of the prior austenite grain size decreased the size of subcritical crack nuclei. It is proposed that the arrest and retardation of short crack nuclei are controlled by the austenite grain size and graphite nodule size. This determines the fatigue endurance limit.